Who does what in a household after genocide? Evidence from Rwanda - Kati Schindler (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper investigates the determinants of intra-household time allocation in post-war Rwanda. A decade after the 1994 genocide, Rwanda still bears the demographic impact of the war, in which at least 800,000 people died and the majority of casualties were adult males. The paper explores two unique features: exogenous variation in household types and large variation in regional cohort-specific sex ratios. Results indicate that, first, exposure to violence and male death can be a trigger of change in gender roles. Second, there is little flexibility to negotiate responsibilities within the household. Third, the local marriage market impacts the division of labor. Young, unmarried women engage more intensely in typical female activities when the shortage of men is severe. Conforming to the female gender role may be a strategy to improve their chances to marry.
Keywords: J12; J22; O12; 330; Conflict; gender roles; Rwanda; time allocation; Haushaltsökonomik; Zeitverwendung; Geschlecht; Soziale Rolle; Verbrechen gegen die Menschlichkeit; Ruanda